Profil Lipid Perokok Konvensional pada Pekerja Bengkel Motor di Jalan Wolter Monginsidi Semarang - Nurul Qomariyah; Fitriani Kahar; Iin Desmiany Duri; Aqilah Defri Ramadhanty; Fadillah Zaskia Putri; Aqilla Hasnu Rajwa (Jaringan Laboratorium Medis, 2026)
Cardiovascular disease is the leading cause of death globally and one of the main risk factors is impaired lipid profiles due to smoking habits (Naomi et al., 2021). Smoking has a significant effect on lipid metabolism. Several studies have shown that smoking habits can cause increased levels of total cholesterol, LDL (Low Density Lipoprotein), and triglycerides, and decreased levels of HDL (High Density Lipoprotein) (Amalia, n.d.) 2018. This imbalance contributes to the risk of cardiovascular disease, atherosclerosis and coronary heart disease (Amalia, n.d.). This study aims to determine the lipid profile of conventional smokers in motorcycle repair shop workers on Jalan Wolter Monginsidi Semarang Method: This study is a descriptive quantitative study with a cross-sectional approach. Analysis Results Lipid profile levels of conventional smokers in motorcycle repair shop workers on Jalan Wolter Munginsidi total cholesterol levels showed significant differences between smoker groups with a p value = 0.010. The average total cholesterol level in light smokers was 141.92±18.97 mg/dL, moderate smokers 150.76±26.86 mg/dL, and heavy smokers 207.70±50.13 mg/dL. This indicates that the heavier the smoker classification, the higher the total cholesterol level. For triglyceride, LDL, and HDL levels, although there were differences in the mean between groups, the statistical test results did not show a significant difference (p>0.05). This indicates that the number of cigarettes consumed per day has a greater influence on increasing total cholesterol levels than other lipid parameters. Conclusion: The number of cigarettes consumed per day has a greater influence on increasing total cholesterol levels than other lipid parameters.